Implikasi Perlindungan Hak Asasi Manusia Dalam Hukum Pidana - Rambe, Rahmansyah Fadlul Al Karim; Sihombing, Muhammad Aufa Abdillah; Winata P, Nurhoneyda (Universitas Medan Area, 2024)
This study aims to examine and analyze the implications of human rights protection in criminal law. The results of the study indicate that human rights protection is one of the important principles in criminal law. Human rights protection in criminal law aims to ensure that everyone suspected or accused of committing a crime receives fair and humane treatment. Human rights protection has become a major focus in the context of criminal law in various countries. This article explores the implications arising from human rights protection within the criminal law framework. In this context, the main focus is on how human rights principles influence the formation, application, and implementation of criminal law. This article discusses the basic concept of human rights and its relationship to criminal law. Then, emphasis is placed on the role of human rights in influencing the legislative process, law enforcement, and criminal sentencing. The consequences of human rights violations in the context of criminal law are also debated in depth. Thus, a thorough understanding of the implications of human rights protection in criminal law is essential to ensure that the legal system can maintain the right balance between justice, individual protection, and effective law enforcement.